2009
DOI: 10.1017/s1368980009005783
|View full text |Cite
|
Sign up to set email alerts
|

The health and nutrition of young indigenous women in north Queensland – intergenerational implications of poor food quality, obesity, diabetes, tobacco smoking and alcohol use

Abstract: Objective: To document nutritional status and health behaviours of young indigenous women of childbearing age in rural communities in north Queensland. Design: Cross-sectional survey of 424 Aboriginal and 232 Torres Strait Islander (TSI) women aged 15-34 years, conducted in twenty-three rural and remote communities of far north Queensland in 1999-2000, with follow-up of a smaller cohort (n 132) in 2006-2007. Main outcome measures: Weight, waist circumference, intake of fruit and vegetables, smoking, alcohol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 37 publications
(39 reference statements)
0
38
1
2
Order By: Relevance
“…Practitioners reported that they generally adhered closely to lifestyle recommendations for smoking and obesity, which have increased prevalence in Aboriginal women and are additional risks for poor pregnancy outcomes [31].…”
Section: Discussionmentioning
confidence: 99%
“…Practitioners reported that they generally adhered closely to lifestyle recommendations for smoking and obesity, which have increased prevalence in Aboriginal women and are additional risks for poor pregnancy outcomes [31].…”
Section: Discussionmentioning
confidence: 99%
“…Only some of the increase can be explained by increasing maternal age, increasing use of assisted reproductive technologies and consequently increased numbers of multiple conceptions. Recent data suggest that even in developed countries, maternal nutritional status is suboptimal in many women of child-bearing age (Inskip et al 2009; Jacobs-Starkey et al 2001; McDermott et al 2009). Dieting (Johnstone et al 2005; Johnstone et al 2008), and both low and high extremes of body mass index (Han et al 2011), are associated with an increased risk for preterm birth and may also affect fetal development (Poston et al 2011; Haugen et al 2005).…”
Section: Late Preterm Birthmentioning
confidence: 99%
“…For Aboriginal and Torres Strait Islander peoples (hereafter referred to as Indigenous Australians), the situation is dire with Indigenous Australians 1.9 times more likely to die of lung cancer Rates of smoking vary within and between Indigenous communities with significantly higher rates reported for Indigenous populations (41%) compared with non-Indigenous Australians (16%) [2]. Remoteness and younger age appear to be critical risk factors for higher rates of smoking among Indigenous Australians with rates as high as 62% reported for women aged 15 to 34 years in a remote community in North Queensland [3] and 76% among men in a community in the Northern Territory [4].…”
Section: Introductionmentioning
confidence: 99%